Jabatan Hal Ehwal Agama Islam Kelantan (JAHEAIK) : It's contributions to the growth of da'wah in Kelantan - Nor Akmal Hayati Bt Abdullah (Kolej Universiti Islam Malaysia, 2011)
This academic project will outline the development and roles of Jabatan Hal Ehwal Agama Islam Kelantan (JAHEAIK) or the Department of Islamic Welfare Kelantan, as a da'wah organization and it's contribution towards the islamisation process in the state of Kelantan. This study covers the early years of the organization from 1979 until the period of reformation in 1998 as well as the background of the department and their function in propagating Islam to the local community including Muslims, non-Muslims, indigenous community, staff from both government and private sector and Muslim converts. Furthermore, this research discusses the growth of Islamic da'wah in Kelantan. So as to obtain an accurate picture of the administration and environment of the department, this study was conducted at the department itself. The researcher has presented a few opinions and recommendations to enhance the quality of this da'wah organization. The researcher's findings indicate that JAHEAIK has implemented da'wah activities by organizing various programmes including talks, courses, theoretical and practical workshop's, propagate Islam to the non-Muslim community in the state, and monitors and enforce Islamic legislation as well as state enactments to those who deviate against Islamic practices. Nevertheless, these efforts must be increased to attain better results in the future.